Black soybean-derived peptides exerted protective effect against alcohol-induced liver injury in mice. (December 2021) - Ren, Jian; Li, Sijin; Song, Chunli; Sun, Xiaohong; Liu, Xiaolan
Graphical abstract: Highlights: Black soybean peptides (BSPs) are rich in oligopeptides (MW < 1, 996 Da) and Lys. BSPs particularly high does group decreased the ALT, AST, TG and Cr levels. BSPs increased GSH, SOD, CAT levels and decreased MDA, IL-6, IL-1β contents. Amino acid composition, antioxidant and anti-inflammatory activities of BSPs are vital for the effect. Abstract: Alcoholic liver disease is one of the most prevalent chronic diseases that causes high morbidity and mortality worldwide. This study demonstrated the protective potential of Alcalase-black soybean-derived peptides (BSPs) against alcohol-induced liver injury in mice. BSPs were rich in oligopeptides (80%, w/w, <1, 996 Da) and Lys. The median and high doses of BSPs (400–800 mg/kg·bw) decreased the levels of AST, ALT in serum. Only high dose of BSPs decreased the triglyceride content to normal level ( P > 0.05). All treatments significantly ( P < 0.01) reduced the creatinine level compared to the model group. The histopathological examination further confirmed the protective effect of BSPs. This protective effect is possibly attributed to the antioxidant and anti-inflammatory activities of BSPs due to the increased levels of GSH, SOD and CAT and decreased contents of MDA, IL-6 and IL-1β compared to those of model group.